2019
DOI: 10.18546/rfa.03.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Brushed under the carpet: Examining the complexities of participatory research

Abstract: Participatory research is sometimes difficult and risky, but there is a paucity of opportunities – and some reluctance – to reflect on its challenging aspects. In this article, we present subjective accounts of our everyday experiences of conducting participatory research as women researchers. We focus on four themes from our combined research experiences to explore some of the frustrations we encounter in participatory research. We argue that it is crucial to identify, reflect upon and address such aspects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 29 publications
0
46
0
1
Order By: Relevance
“…In this collaborative project between members of the academy and the community for the production of knowledge with the potential for social changes, challenges imposed by gender identity and sexuality are foreseen, even requiring the negotiation of social roles. As warned by Lenette et al 29 participatory research is associated with social movements -as reported herewhich are generally conducted by female scientists who experience the impact of their gender on fieldwork. Being female scientists in participatory research brings investigators closer to the feminist perspective, of which the ultimate goals focus on caring for the other, empowerment, and social justice.…”
Section: Methodological Reflection and Fieldmentioning
confidence: 75%
See 1 more Smart Citation
“…In this collaborative project between members of the academy and the community for the production of knowledge with the potential for social changes, challenges imposed by gender identity and sexuality are foreseen, even requiring the negotiation of social roles. As warned by Lenette et al 29 participatory research is associated with social movements -as reported herewhich are generally conducted by female scientists who experience the impact of their gender on fieldwork. Being female scientists in participatory research brings investigators closer to the feminist perspective, of which the ultimate goals focus on caring for the other, empowerment, and social justice.…”
Section: Methodological Reflection and Fieldmentioning
confidence: 75%
“…Humanization as a concept-experience provides the basis for expanding its ethical-aesthetic-political use in the field of obstetric care through a (new) analytical-evaluative look, in order to (trans)form the realities of work and care. 15 This proposal is aligned with the gap identified in Brazilian health research 29 regarding the distance in know-how, that is, a Display 5. Recommendations for a multi-site international research action plan.…”
Section: Discussionmentioning
confidence: 89%
“…Data can be compiled, compared, abstracted, and analyzed, leading to fundamental theories of data involving aspects such as scaling, measuring, categorizing, and connecting the information [ 74 , 75 , 76 ]. These decisions and interpretations lead to bias [ 50 ], meaning that data cannot be taken as neutral or objective, with some authors even questioning what data would be legitimate [ 57 ]. As [ 77 ] (p. 45) notes, “Data is in the eye of the beholder”.…”
Section: Data-related Challengesmentioning
confidence: 99%
“…The roles of academics and of academia within participatory research have been called into question [ 55 , 56 ] along with the risks and alleged inconsistencies which emerge due to the realities of dealing with people during fieldwork [ 57 ]. Based on these cautions, both healthcare and disaster researchers query how participatory such research necessarily is and especially where improvements ought to be enacted, because they document similar challenges in applying it for healthcare, DRR, their links, and their broader contexts [ 58 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…PAR scholars place the assessment of quality and critical reflection high on the agenda (Dedding and Slager 2013; International Collaboration for Participatory Health Research (ICPHR) 2013; Cook et al 2017;Abma et al 2019;Banks and Brydon-Miller 2019;Abma et al 2017;Lennette et al 2019). These scholars point to the ideal and rhetoric of participation and call for creative solutions, asking PAR practitioners to engage in selfanalysis of the tensions they encounter in conducting democratic collaborative research.…”
Section: Introductionmentioning
confidence: 99%